Chromosomal changes during development and progression of prostate adenocarcinomas - Zitzelsberger, H (Nature Publishing Group, 2001)
Chromosomal copy number changes were investigated in 16 prostate carcinomas, 12 prostatic intraepithelial neoplasias (PIN; 4 low-grade and 8 high-grade) adjacent to the invasive tumour areas, and 5 regional lymph node metastases. For this purpose, comparative genomic hybridization (CGH) was performed and a copy number karyotype for each histomorphological entity was created. CGH on microdissected cells from non-neoplastic glands was carried out on 3 different cases to demonstrate the reliability of the overall procedure. None of the non-neoplastic tissue samples revealed chromosome copy number changes. In PIN areas, chromosomal imbalances were detected on chromosomes 7, 8q, Xq (gains), and on 4q, 5q, 8p, 13q and 18q (losses). In the primary tumours, recurrent (at least 25% of cases) gains on chromosomes 12q and 15q, and losses on 2q, 4q, 5q, Xq, 13q and 18q became apparent. Losses on 8p and 6q as well as gains on 8q and of chromosome 7 were also detected at lower frequencies than previously reported. The pooled CGH data from the primary carcinomas revealed a novel region of chromosomal loss on 4q which is also frequently affected in other tumour entities like oesophageal adenocarcinomas and is supposed to harbour a new tumour suppressor gene. Gains on chromosome 9q and of chromosome 16 and loss on chromosome 13q were observed as common aberrations in metastases and primary tumours. These CGH results indicate an accumulation of chromosomal imbalances during the PIN–carcinoma–metastasis sequence and an early origin of tumour-specific aberrations in PIN areas. © 2001 Cancer Research Campaign http://www.bjcancer.com